Do African Children Have an Equal Chance?: A Human Opportunity Report for Sub-Saharan Africa - Dabalen, Andrew (World Bank, 2015)
We have long known that a person's chance of success in life is deeply influenced by early access to education, health services, safe water, and nutritious food. This in turn improves the likelihood that a child can live up to his or her human potential and pursue a rewarding life. As Sub-Saharan Africa (SSA) enters its 20th year of unprecedented high economic growth and hopes continue to rise, its citizens increasingly wonder if these more hopeful economic times will translate into a better future for themselves and their families.